Vector bundles on plane cubic curves and the classical Yang-Baxter equation - Burban, Igor; Henrich, T. (Journal of the European Math. Society)

Mathematikbezogene Kompetenzentwicklung elementarpädagogischer Fachpersonen in Intensiv-Fortbildungen - Bruns, Julia; Eichen, L. (Beiträge zum Mathematikunterricht 2015)

Entwicklung eines videobasierten Instruments zur Erhebung von Handlungsfähigkeiten elementarpädagogischer Fachpersonen im mathematischen Bereich (VimaH) - Bruns, Julia; Eichen, L. (Entwicklung mathematischer Fähigkeiten von Kindern im Grundschulalter – Tagungsband des AK Grundschule in der GDM 2015)

Entwicklung eines videobasierten Instruments zur Erhebung mathematikdidaktischer Handlungskompetenzen elementarpädagogischer Fachpersonen - Bruns, Julia; Eichen, L. (Beiträge zum Mathematikunterricht 2015)

Adaptive Förderung zur Vorbereitung auf den Übergang vom Elementar- in den Primarbereich am Beispiel des Bereichs Mathematik - Bruns, Julia; Eichen, Lars (Frühe Bildung)
Die vorliegende quasi-experimentelle Querschnittsuntersuchung verfolgt das Ziel, adaptive Förderleistungen elementarpädagogischer Fachpersonen zu erfassen und Zusammenhänge mit anderen Komponenten elementarpädagogischer Arbeit aufzudecken. Im Zentrum steht die Frage: Welcher Zusammenhang zeigt sich zwischen der Beobachtungsintensität, den diagnostischen Fähigkeiten und der Qualität der adaptiven Förderpraxis im Elementarbereich? Fokussiert wird die adaptive Förderleistung einer Teilstichprobe mit n = 31 Fachpersonen in Bezug auf die Teilstichprobe von n = 62 Kinder. Dazu werden verschiedene Methoden auf Kinder- und Fachpersonenebene im Sinne eines mixed-methods Designs miteinander verknüpft (Mathematiktest ‚zahlenstark‘, standardisierte Beobachtung, standardisiertes Interview). Die Ergebnisse zeigen, dass keiner Fachperson eine optimale Förderung zweier Kinder gelingt. Im Hinblick auf den Übergang zwischen Elementar- und Primarbereich kann gefolgert werden, dass die Kinder unzureichend in ihren individuellen Bildungsprozessen begleitet werden.
Keywords: General Earth and Planetary Sciences; General Environmental Science

Aging in digital circuits and age monitoring: Object-oriented modeling and evaluation - Sadeghi-Kohan, Somayeh; Kamran, Arezoo; Forooghifar, Farnaz; Navabi, Zainalabedin (2015 10th International Conference on Design & Technology of Integrated Systems in Nanoscale Era (DTIS))
Transistor and interconnect wearout is accelerated with transistor scaling resulting in timing variations and consequently reliability challenges in digital circuits. Age monitoring methods can be used to predict and deal with the aging problem. Selecting appropriate locations for placement of hardware aging monitors is an important issue. In this work we propose a procedure for selection of appropriate internal nodes in combinational clouds between pipeline stages or combinational parts of a sequential circuit to place hardware monitors that can effectively provide aging information of various components of a modern digital system. In order to implement the node selection procedure, we propose an object-oriented model. Object-oriented model of a circuit along with a probabilistic and logical simulation engine that we have developed can effectively be used for implementation and also fast evaluation of the proposed node selection mechanism. The proposed object-oriented C+ + models can be integrated into a SystemC RTL model making it possible to perform mixed-level simulation, and integrated evaluation of a complete system. We have applied our proposed scheme to several processors including MIPS, ARM, ALPHA and MiniRISC and have looked at its effectiveness for these processors.

Online self adjusting progressive age monitoring of timing variations - Sadeghi-Kohan, Somayeh; Kamal, Mehdi; McNeil, John; Prinetto, Paolo; Navabi, Zain (2015 10th International Conference on Design & Technology of Integrated Systems in Nanoscale Era (DTIS))
Transistor and interconnect wearout is accelerated with transistor scaling that results in timing variations. Progressive age measurement of a circuit can help a better prevention mechanism for reducing more aging. This requires age monitors that collect progressive age information of the circuit. This paper focuses on monitor structures for implementation of progressive age detection. The monitors are self-adjusting that they adjust themselves to detect progressive changes in the timing of a circuit. Furthermore, the monitors are designed for low hardware overhead, and certainty in reported timing changes.

Exploring Tradeoffs between Specialized Kernels and a Reusable Overlay in a Stereo-Matching Case Study - Kenter, Tobias; Schmitz, Henning; Plessl, Christian (International Journal of Reconfigurable Computing (IJRC))
FPGAs are known to permit huge gains in performance and efficiency for suitable applications but still require reduced design efforts and shorter development cycles for wider adoption. In this work, we compare the resulting performance of two design concepts that in different ways promise such increased productivity. As common starting point, we employ a kernel-centric design approach, where computational hotspots in an application are identified and individually accelerated on FPGA. By means of a complex stereo matching application, we evaluate two fundamentally different design philosophies and approaches for implementing the required kernels on FPGAs. In the first implementation approach, we designed individually specialized data flow kernels in a spatial programming language for a Maxeler FPGA platform; in the alternative design approach, we target a vector coprocessor with large vector lengths, which is implemented as a form of programmable overlay on the application FPGAs of a Convey HC-1. We assess both approaches in terms of overall system performance, raw kernel performance, and performance relative to invested resources. After compensating for the effects of the underlying hardware platforms, the specialized dataflow kernels on the Maxeler platform are around 3x faster than kernels executing on the Convey vector coprocessor. In our concrete scenario, due to trade-offs between reconfiguration overheads and exposed parallelism, the advantage of specialized dataflow kernels is reduced to around 2.5x.

Easy-to-Use On-The-Fly Binary Program Acceleration on Many-Cores - Damschen, Marvin; Plessl, Christian (Proceedings of the 5th International Workshop on Adaptive Self-tuning Computing Systems (ADAPT))
This paper introduces Binary Acceleration At Runtime(BAAR), an easy-to-use on-the-fly binary acceleration mechanismwhich aims to tackle the problem of enabling existentsoftware to automatically utilize accelerators at runtime. BAARis based on the LLVM Compiler Infrastructure and has aclient-server architecture. The client runs the program to beaccelerated in an environment which allows program analysisand profiling. Program parts which are identified as suitable forthe available accelerator are exported and sent to the server.The server optimizes these program parts for the acceleratorand provides RPC execution for the client. The client transformsits program to utilize accelerated execution on the server foroffloaded program parts. We evaluate our work with a proofof-concept implementation of BAAR that uses an Intel XeonPhi 5110P as the acceleration target and performs automaticoffloading, parallelization and vectorization of suitable programparts. The practicality of BAAR for real-world examples is shownbased on a study of stencil codes. Our results show a speedup ofup to 4 without any developer-provided hints and 5.77 withhints over the same code compiled with the Intel Compiler atoptimization level O2 and running on an Intel Xeon E5-2670machine. Based on our insights gained during implementationand evaluation we outline future directions of research, e.g.,offloading more fine-granular program parts than functions, amore sophisticated communication mechanism or introducing onstack-replacement.

Improving Packet Processing Performance in the ATLAS FELIX Project – Analysis and Optimization of a Memory-Bounded Algorithm - Schumacher, Jörn; T. Anderson, J.; Borga, A.; Boterenbrood, H.; Chen, H.; Chen, K.; Drake, G.; Francis, D.; Gorini, B.; Lanni, F.; Lehmann-Miotto, Giovanna; Levinson, L.; et al. (Proc. Int. Conf. on Distributed Event-Based Systems (DEBS))